(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study was conducted to determine the structure of benthic invertebrates community, as well as a study of some factors associated with water quality in Shatt Al-Kufa. The study was included a choice of three sites located along the Shatt Al-Kufa River, water samples and benthic invertebrates were collected during the period from February 2014 to January 2015. The abiotic study included measurements of chlorophyll a, salinity, total dissolved solids, biochemical oxygen demand, total hardness, nitrate, and sulfate. The biotic study included the determination the composition of the benthic invertebrates community through the study of the mean population density, the relative abundance index of these organisms and the Jaccard Coefficient was calculated to identify the value of similarity between the studied sites. In the present study, 28 taxa of benthic invertebrates were recorded belong to 4 main groups which are: 8 taxa belonged to Annelida, 7 belonged to Insecta, 10 belonged to Mollusca, 3 belonged to Nematoda. Annelida recorded the highest percentage 40.8% of the total number of benthic invertebrates, Insecta with 30.3%, Mollusca and Nematoda with 28.4 %, 0.5% respectively. Benthic invertebrate has shown positive and negative relationships with the studied physical and chemical characteristics.